EFL Students’ Perception of Interaction in Online Learning Practices - Hanik Nurul Faizah; Suwandi Suwandi; Hendi Pratama (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This research investigates the English Foreign Language (EFL) lecturers' and students' perceptions of learning interactions when teaching-learning was conducted online during the pandemic of covid-19. The interaction concerned in this study included students-student interaction, student-lecturer interaction, and student-content interaction. Purposive sampling is used to determine the respondents of this study. The data were collected from 106 university students of non-English education majors through a questionnaire in one of the universities in Semarang. Additionally, an interview is used to get in-depth information on the students' perceptions. This study is a case study using a qualitative approach supported by a quantitative approach. The result shows that students tend to perceive student-student and student-lecturer interaction positively. However, they perceive student-content interaction quite negatively.